2019
DOI: 10.1055/a-1045-1989
|View full text |Cite
|
Sign up to set email alerts
|

Endolichenic fungal diversity associated with some lichens of the Western Ghats

Abstract: A total of 389 strains of fungi belonging to 38 species were isolated from 10 lichen species of the Western Ghats, southern India. All the lichens screened, irrespective of their growth forms or location, harboured endolichenic fungi. Most of the fungi belonged to the Ascomycotina. Chaetomium sp. 1, Hypoxylon investiens, Nemania bipapillata, Nodulisporium sp., Paecilomyces sp., and Sporormiella intermedia were the most common ones and were present in 5 or more lichen species. Of the 28 sporulating fungi, 7 bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Several studies observed Sordariomycetes-dominant patterns in ELF communities [ 8 , 15 , 39 , 40 , 41 ]. The most abundant species, Daldinia childiae complex, was isolated from all individual lichen samples and under all isolation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies observed Sordariomycetes-dominant patterns in ELF communities [ 8 , 15 , 39 , 40 , 41 ]. The most abundant species, Daldinia childiae complex, was isolated from all individual lichen samples and under all isolation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among the Antarctic lichens, Park et al (2015) reported Arthoniomycetes, Eurotiomycetes, and Lecanoromycetes as the most common classes [54], whereas in a later study, Yu et al (2018) found Leotiomycetes, Sordariomycetes, and Dothideomycetes to be abundant [22]. Similarly, Muggia et al (2016) found that Chaetothyriomycetes and Dothideomycetes were the major fungal classes among rock-inhabiting lichens in the alpine area, whereas Rajulu et al (2019) found Sordariomycetes, Dothideomycetes, and Eurotiomycetes to be prevalent among lichens in the Western Ghats, India [55,56]. The findings of these studies show that the environment, growth substrate, and a variety of other abiotic variables influence the fungal diversity associated with lichens.…”
Section: Discussionmentioning
confidence: 95%